2(t-1)-5(3t-7)=10-6(5t+4)

Simple and best practice solution for 2(t-1)-5(3t-7)=10-6(5t+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(t-1)-5(3t-7)=10-6(5t+4) equation:


Simplifying
2(t + -1) + -5(3t + -7) = 10 + -6(5t + 4)

Reorder the terms:
2(-1 + t) + -5(3t + -7) = 10 + -6(5t + 4)
(-1 * 2 + t * 2) + -5(3t + -7) = 10 + -6(5t + 4)
(-2 + 2t) + -5(3t + -7) = 10 + -6(5t + 4)

Reorder the terms:
-2 + 2t + -5(-7 + 3t) = 10 + -6(5t + 4)
-2 + 2t + (-7 * -5 + 3t * -5) = 10 + -6(5t + 4)
-2 + 2t + (35 + -15t) = 10 + -6(5t + 4)

Reorder the terms:
-2 + 35 + 2t + -15t = 10 + -6(5t + 4)

Combine like terms: -2 + 35 = 33
33 + 2t + -15t = 10 + -6(5t + 4)

Combine like terms: 2t + -15t = -13t
33 + -13t = 10 + -6(5t + 4)

Reorder the terms:
33 + -13t = 10 + -6(4 + 5t)
33 + -13t = 10 + (4 * -6 + 5t * -6)
33 + -13t = 10 + (-24 + -30t)

Combine like terms: 10 + -24 = -14
33 + -13t = -14 + -30t

Solving
33 + -13t = -14 + -30t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '30t' to each side of the equation.
33 + -13t + 30t = -14 + -30t + 30t

Combine like terms: -13t + 30t = 17t
33 + 17t = -14 + -30t + 30t

Combine like terms: -30t + 30t = 0
33 + 17t = -14 + 0
33 + 17t = -14

Add '-33' to each side of the equation.
33 + -33 + 17t = -14 + -33

Combine like terms: 33 + -33 = 0
0 + 17t = -14 + -33
17t = -14 + -33

Combine like terms: -14 + -33 = -47
17t = -47

Divide each side by '17'.
t = -2.764705882

Simplifying
t = -2.764705882

See similar equations:

| 8(5+6p)+8=240 | | 7v-7=14 | | 8x+5=12-3x | | -24-(-13)=x | | -3(3a-5)+7=94 | | 2x^2+6x-13=0 | | (-5)=-3(-5)+4(-5)-8 | | -7x+3=-7 | | 3x^2-8x-81=0 | | -3y+15=1 | | 200-13y=7y | | -46-(-46)=x | | 107=-5+7(-4x+4) | | 0.2(p-16)=0.4p | | 12x-9=-4x+7 | | 5y-1=3y+11 | | 3x-4=71 | | 3z+2(6-z)=-(z-2)+4 | | 4-3x=71 | | 3+4x=3x+7 | | 4m-18=15-12 | | 9b^2-11=6b | | y=-11 | | 9v-4=13 | | 2z-4(z+1)=-(5z+6)+z | | 4a-9=7a+6 | | 14y+6=12y+9 | | 9p=5(7p+8) | | 18=-10-7a | | 15+8x=57-6x | | 0=6a+9a^2 | | -34-(-6)=7 |

Equations solver categories